'Space of Possibles'? Legitimacy, Industry Maturity, and Organizational Foresight1. (May 2014) - Stringfellow, Lindsay; Maclean, Mairi
<x xml:space="preserve">Abstract</x> The dispositions and invisible cognitive structures central to organizational foresight are more likely to emerge in young or transforming industries, which are less constrained by the need to achieve institutional legitimacy.